The Ideology of Accent: Investigating Accent-Based Judgments Among Indonesian EFL Students - Ashar, Aisyah; Khartha, Aqzhariady; Hidayat Nasir, Syarif; Pratiwi, Alifiah (Jurnal Paedagogy, 2026)
This study aims to investigate accent-based judgments among Indonesian learners of English as a Foreign Language (EFL), particularly the preference for native-like English accents over communicative competence. The research employed a mixed-method design involving a questionnaire distributed to 60 English Education students selected through purposive sampling and semi-structured interviews with 15 selected participants from the same cohort at Universitas Sembilanbelas November Kolaka. The questionnaire data were analyzed using descriptive statistics, while interview data were examined through thematic analysis. The findings reveal that most students prioritize native-like accents, especially British English, as the primary indicator of speaking proficiency, even when fluency and grammatical accuracy are weak. This preference contributes to social favoritism in academic contexts and leads to internalized insecurity among fluent speakers with Indonesian-accented English. The study highlights how accent ideology influences peer judgment and learner identity, reinforcing native-speakerism within EFL classrooms. It concludes by advocating an intelligibility-oriented approach to English teaching and the inclusion of diverse English varieties to promote more equitable and inclusive language practices.